Alzheimer’s disease biological PET staging using plasma p217+tau - Azadeh Feizpour; Vincent Doré; Natasha Krishnadas; Pierrick Bourgeat; James D. Doecke; Ziad S. Saad; Gallen Triana-Baltzer; Simon M. Laws; Rosita Shishegar; Kun Huang; Christopher Fowler; Larry Ward; et al. (Communications Medicine)
Abstract Background Plasma phospho-tau biomarkers, such as p217+tau, excel at identifying Alzheimer’s disease (AD) neuropathology. However, their ability to substitute for tau PET to identify AD biological stage is unclear. Methods Participants included 248 cognitively unimpaired (CU) and 227 cognitively impaired (CI) individuals, with Janssen plasma p217+tau Simoa® assay, 18F-NAV4694 Aβ-PET (A) and 18F-MK6240 tau-PET (T) data. Biological PET stages were defined according to the Revised Criteria for Diagnosis and Staging of Alzheimer’s Disease (2024): Initial (A + T-), Early (A + TMTL + ), Intermediate (A + TMOD + ), and Advanced (A + THIGH + ). The threshold for A+ was 25 Centiloid and for THIGH + , the 75th percentile SUVRtemporo-parietal in A + CI. Sixty percent were A + , 36% Intermediate/Advanced, and 9% Advanced. The performance of p217+tau in discriminating AD stages was assessed using Receiver Operating Characteristic (ROC) analysis and logistic regression. Results Plasma p217+tau concentrations increase across the AD biological PET stages, except between Initial and Early stages. Screening for all AD stages (vs. A-T-), combined Intermediate/Advanced stages, or Advanced stage yields AUC of 0.92, 0.92, and 0.91, respectively (CI only: AUC 0.93, 0.89, 0.83). Plasma p217+tau Youden threshold provides sensitivity of 0.77 [0.73–0.90], specificity 0.91 [0.80–0.95], PPV 0.84 [0.71–0.89], and NPV 0.88 [0.85–0.93] for combined Intermediate/Advanced stages. For the Advanced stage alone, sensitivity is 0.89 [0.79–0.97], specificity 0.82 [0.75–0.9], NPV 0.99 [0.98–1.0], but PPV is only 0.33 [0.25–0.47]. Conclusions In addition to accurately screening for A+ individuals, plasma p217+tau is useful for identifying a combined Intermediate/Advanced stage AD cohort or pre-screening to reduce the tau-PET required to identify Advanced stage AD individuals.